Organisational Commitment Influenced by Motivation and Training with Job Satisfaction and Performance as Mediator: Case Study at Starbucks Regional VII Indonesia - Aris Budiono (Yayasan Literasi Sains Indonesia, 2024)
This research aims to analyse organisational commitment, which is influenced by motivation and training, with job satisfaction and performance as mediation. Research data was developed using a Likert scale. The research population was 210 employees. Using Morgan tables, research data was obtained for 156 respondents, including 20 people who were intended to test the validity and reliability of the measuring instrument. We use quantitative methods with multilevel linear regression. The IBM SPSS 24 statistical application was used for statistical calculations on the three substructures in the measurements. This research concludes: 1. The influence of organisational commitment can be directly influenced by motivation, performance and job satisfaction but is not influenced by the training received. Employee job satisfaction is influenced by motivation and training. Employee performance can be influenced by motivation and training. 2. The indirect effect on the organisational commitment variable is influenced by motivation both through job satisfaction and performance, and organisational commitment is not influenced by training through performance. Even so, performance can be a mediating variable between motivation and organisational commitment.